AGE AS A KEY RISK FACTOR FOR SEVERE RESPIRATORY SYNCYTIAL VIRUS INFECTION IN CHILDREN: A LITERATURE REVIEW - Agata Rapior; Julia Groszewska; Agata Mytych; Michał Romaniuk; Daria Julia Makowska-Woszczyk; Kinga Lubomska; Patrycja Jagura; Jan Romaniuk; Marta Dziedziak; Łukasz Nosek (International Journal of Innovative Technologies in Social Science, 2026)
Research Objectives: Respiratory Syncytial Virus (RSV) is a leading cause of lower respiratory tract infections in young children, particularly in infants under six months. This review aims to synthesize recent clinical and epidemiological data to identify age groups at the highest risk for severe RSV disease. Methods: A systematic literature search was conducted in PubMed for studies published between 2020 and 2025, focusing on pediatric populations aged 0–5 years with laboratory-confirmed RSV infection. Cohort, prospective, and retrospective studies, as well as clinical guidelines, reporting hospitalization rates, intensive care unit admissions, oxygen therapy, and risk factors such as prematurity and comorbidities were included. Data were analyzed narratively to assess relationships between age, prematurity, comorbidities, and disease severity. Key Findings: The youngest infants (0–5 months) accounted for most hospitalizations and were most likely to require intensive care. Prematurity increased hospitalization risk approximately with earlier gestational age correlating with higher severity. Comorbidities further elevated the risk of prolonged hospitalization and intensive care, especially in older children. Introduction of RSV prophylaxiy substantially reduced hospitalization rates among infants, particularly those 0–2 months. Seasonal trends and epidemiological shifts, influenced by the COVID-19 pandemic, affected RSV incidence and severity. Conclusions: Age is the primary determinant of severe RSV outcomes, with prematurity and comorbidities acting as significant modifiers. Early identification of high-risk infants and targeted prophylactic strategies are essential to reduce hospitalization and optimize healthcare resource allocation. Continuous monitoring and evaluation of prevention strategies across age groups remain crucial.